Pendampingan Bimbingan Belajar Bahasa Inggris dan Bakti Sosial di Yayasan Pendidikan dan Sosial Roudlotut Thullab - Agustina, Eka; Rohmah, Ainur; Kuspiyah, Hastuti Retno (Jurnal Indonesia Mengabdi, 2019)
This community service stems from the anxiety of the English Education Study Program lecturers on the importance of the usefulness of the knowledge possessed by lecturers for better community education outside of educational activities on campus. Raudhatul Thullab's educational and social foundation lacks teaching staff, especially English teachers, while students who are high enough to speak English. The object/target of this service is Raudhatul Thullab Middle School and Vocational High School students, in carrying out this service that is with a learning assistance model that is conducted for 1 month. The material includes grammar, reading, speaking, pronunciation and writing. The results of community service activities received a positive response from the school, especially because this training was suitable for their needs. The motivation of the trainees was quite enthusiastic. This indicates a desire to improve their abilities in mastering English.